Evaluating pharmacist prescribing education programmes: a realist synthesis protocol - Charlotte E Rees; Sarah Dineen-Griffin; Shalom I Benrimoj; Kristin Xenos; Ian Murray Heslop (BMJ Open)
Introduction Pharmacist prescribing has evolved to meet healthcare system needs, but the effectiveness, mechanisms and contextual factors influencing education programmes remain poorly understood. Realist approaches are fairly novel in pharmacy practice research. This realist synthesis aims to answer the question: to what extent do pharmacy prescribing education programs work (or not), for whom and under what circumstances, and why?Methods and analysis A realist methodology (realist synthesis) will be used to review the outcomes of programmes. Pawson’s key stages will be followed: (1) clarifying the scope; (2) determining the search strategy; (3) study selection; (4) extracting and analysing data; and (5) synthesising findings and drawing conclusions. The synthesis will follow Realist And Meta-narrative Evidence Syntheses–Evolving Standards publication guidelines. Data extracted will include the study characteristics, alongside the contexts, mechanisms and outcomes of varied pharmacy prescribing education programmes. The search strategy will include searching PubMed, Scopus, Web of Science and CINAHL Complete. An initial programme theory will use selected grey literature. Context-mechanism-outcome configurations will be identified, and recurring patterns will be synthesised to refine the initial programme theory.Ethics and dissemination Ethics approval is not required. Dissemination will be sought via peer-reviewed academic conferences and journals.PROSPERO registration number CRD420251056576.